Analysis of Embryoid Bodies Derived from Human Induced Pluripotent Stem Cells as a Means to Assess Pluripotency - Steven D. Sheridan; Vasudha Surampudi; Raj R. Rao (Stem Cells International)
Human induced pluripotent stem cells (hiPSCs) have core properties of unlimited self-renewal and differentiation potential and have emerged as exciting cell sources for applications in regenerative medicine, drug discovery, understanding of development, and disease etiology. Key among numerous criteria to assess pluripotency includes the in vivo teratoma assay that has been widely proposed as a standard functional assay to demonstrate the pluripotency of hiPSCs. Yet, the lack of reliability across methodologies, lack of definitive clinical significance, and associated expenses bring into question use of the teratoma assay as the “gold standard” for determining pluripotency. We propose use of the in vitro embryoid body (EB) assay as an important alternative to the teratoma assay. This paper summarizes the methodologies for creating EBs from hiPSCs and the subsequent analyses to assess pluripotency and proposes its use as a cost-effective, controlled, and reproducible approach that can easily be adopted to determine pluripotency of generated hiPSCs.